The global prevalence of postpartum psychosis: a systematic review - VanderKruik, Rachel; Barreix, Maria; Chou, Doris; Allen, Tomas; Say, Lale; Cohen, Lee S. (BMC psychiatry, 2017)
Background Mental health is a significant contributor to global burden of disease and the consequences of perinatal psychiatric morbidity can be substantial. We aimed to obtain global estimates of puerperal psychosis prevalence based on population-based samples and to understand how postpartum psychosis is assessed and captured among included studies. Methods In June 2014, we searched PubMed, CiNAHL, EMBASE, PsycINFO, Sociological Collections, and Global Index Medicus for publications since the year 1990. Criteria for inclusion in the systematic review were: use of primary data relevant to pre-defined mental health conditions, specified dates of data collection, limited to data from 1990 onwards, sample size >200 and a clear description of methodology. Data were extracted from published peer reviewed articles. Results The search yielded 24,273 publications, of which six studies met the criteria. Five studies reported incidence of puerperal psychosis (ranging from 0.89 to 2.6 in 1000 women) and one reported prevalence of psychosis (5 in 1000). Due to the heterogeneity of methodologies used across studies in definitions and assessments used to identify cases, data was not pooled to calculate a global estimate of risk. Conclusions This review confirms the relatively low rate of puerperal psychosis; yet given the potential for serious consequences, this morbidity is significant from a global public health perspective. Further attention to consistent detection of puerperal psychosis can help provide appropriate treatment to prevent harmful consequences for both mother and baby.